Peran Guru Bimbingan Konseling Dalam Meningkatkan Kedisiplinan Siswa - Anggun Kurnia Robbani Rosita; Siti Fatihah; Mar’atul Latifah; Mustika Faradilla Shanti (Pusat Riset dan Inovasi Nasional, 2024)
This study uses a qualitative methodology, primarily interview and document analysis techniques, to ascertain the role guidance and counseling teachers play in resolving student discipline issues. The results of the study show that guidance and counseling instructors can use a variety of strategies, including one-on-one counseling, mentoring, and observation, to address a range of issues, including student behavior.